Phytotherapeutic Evaluation of Psidium guajava Leaf Extract on Glycemic Control and Hepatic Function in Alloxan-Induced Diabetic Mice - Aliyu Ladan, Ahmad; Yusuf Idris, Abdul-kareem; Khadija Zirami, Abubakar; Aminu Muhammad, Ahmad; Musa Jibrin, Habib; Khalid Aliyu, Abubakar (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Diabetes mellitus (DM) is one of the most prevailing metabolic disorders, characterized by high level of blood glucose level, which may result from either the pancreas's failure to secrete insulin or the inability of insulin receptors to respond to insulin. Psidium guajava shows promise as effective therapeutic option for this disease management. This study investigated the ameliorative effects of Psidium guajava aqueous leaf extract on blood glucose levels and liver damage in mice with alloxan-induced diabetes (120 mg/kg). Thirty mice (20-35g) were divided into six groups of five. Group I (non-diabetic) received normal saline. Diabetic groups II-VI received: normal saline (II), Metformin (5 mg/kg, III), and Psidium guajava aqueous extract at 150 mg/kg (IV), 300 mg/kg (V), and 450 mg/kg (VI). Diabetes induction was confirmed 72 hours post-administration. Oral gavage administration was conducted daily for a period of 28 days. Blood glucose was estimated on the 14th and 28th day of administration. On the 28th day, animals were euthanized, and blood samples were collected for biochemical analysis. This study's results revealed significant reductions (P<0.05) in liver enzymes (ALT, AST) and blood glucose levels compared to controls, indicating potential hepatoprotective and hypoglycemic effects. The results of this research indicate that Psidium guajava exhibits hepatoprotective effect and alleviate hyperglycemia and may mitigate diabetes-induced hepatic disorders.